Population Dynamics Study of Ribbonfish, Lepturacanthus savala from the North-Eastern Tip of Bay of Bengal (Global Journal of Science Frontier Research, 2018)
Land-based survey data were collected from two major fish landing centers of southeast Bangladesh. A total of 1,770 Lepturacanthus savala in dividuals were collected for lengthfrequency and length-weight analysis. The asymptotic length (L ∞), growth coefficient ( k ), theoretical age with length at zero (t 0 ) and growth performance index (Ø') were estimated to be 111 cm, 0.34 year -1 , -0.34 year and 3.622 respectively. Based on the growth parameters total mortality (Z), natural mortality (M) and fishing mortality (F) was found 1.09 year -1 , 0.611 year -1 , and 0.479 year -1 respectively. The exploitation rate (E) using the length converted catch curve was found as 0.43 year -1 which denotes that the studied population is not in over-exploited condition. Recruitment pattern revealed the peak in July. Length-weight relationship of L. savala was established as W = 0.0381 TL 2.1194 where R 2 = 0.8697.
Keywords: population dynamics; lepturacanthus savala; bay of bengal